If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+13=3(x+5)
We move all terms to the left:
4x+13-(3(x+5))=0
We calculate terms in parentheses: -(3(x+5)), so:We get rid of parentheses
3(x+5)
We multiply parentheses
3x+15
Back to the equation:
-(3x+15)
4x-3x-15+13=0
We add all the numbers together, and all the variables
x-2=0
We move all terms containing x to the left, all other terms to the right
x=2
| 4(x+3)-6=-x-34 | | 3(2x-3)-4=-19 | | 2(4x+3)+3=-x+27 | | -12x+26=-6x+68 | | -2x-22=2(5x+1) | | 3(2x-1)+10=31 | | -21=3(5x-2) | | -9x+7=-5x+31 | | -12=3(x+1) | | 3(2x+3)+8=-4x-13 | | -4x-13=-x-25 | | 25=2(x+5)+9 | | -42=3(2x-5)+9 | | 5(x+1)=-x+29 | | x-3=-4x-38 | | -5x+46=4(3x+3) | | 4x+7=-x-23 | | -3x+3=-x-7 | | -30=3(4x+5)-9 | | -5x+22=-3x+4 | | 10x+5=2x+93 | | -6=2(x-3)-2 | | -5x-12=-3x-20 | | 5(x+3)-9=1 | | -15+2x+x2=0 | | 24+4*8/4)=x | | -23=2(x+1)-9 | | -6=2(x+2) | | 4x+35=4(2x-1)+3 | | 2x+28=46 | | -x-10=-2x-6 | | 10x+24=7x+42 |